Brazilian Digital Transformation Readiness: A Transdisciplinary Engineering Approach in the Automotive Sector - Costa, Anderson Suzuki [UNESP]; Muniz, Jorge [UNESP]; Munyon, Timothy P.; Eriksson, Kristina M. (IOS Press, 2024)
Although widely adopted around the globe, emerging evidence suggests that digitalization investments often underperform. One potential reason is that firms lack organizational readiness to adopt these new technologies. Thus, in this paper, we evaluate both digitalization implementation and digital readiness in the Brazilian auto industry to ascertain how readiness potentially impacts the implementation of new digital technologies and processes. In reviewing the literature on digital transformation in the global automotive sector, a lack of studies was identified on the level of readiness and maturity of the automotive sector in relation to digitalization and innovation brought out by the implementation of Industry 4.0 technologies. To address this gap, a digitalization protocol was drawn up with the aim of verifying the maturity of companies and understanding the degree of readiness for digital transformation. Subsequently, the research was applied to thirteen companies in the automotive sector, including vehicle and engine manufacturers, as well as automotive parts and systems subcontractors in the automotive supply chain. The contribution of this paper identified that the use of digital technologies increases the quality and results of work, facilitates the achievement of objectives, and offers a competitive advantage. Further’ advantages come from improving customer experience, increasing innovation through data analysis, improving manufacturing processes, and bringing greater employee engagement. Finally, it is highlighted that this study is aligned with the ninth Sustainable Development Goal (SDG) proposed by the United Nations: Industry, Innovation, and Infrastructure, which seeks to promote inclusive and sustainable industrialization and foster innovation.
Keywords: Automotive; Digital transformation; Digitalization; Readiness; Transdisciplinary engineering